Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1189/jlb.0103026
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 and TLR4 serve distinct roles in the host immune response against Mycobacterium bovis BCG

Abstract: Toll-like receptor (TLR) proteins mediate cellular activation by microbes and microbial products. To delineate the role of TLR proteins in the development of host immune responses against mycobacteria, wild-type and TLR-deficient mice were infected with nonpathogenic Mycobacterium bovis bacillus Calmette-Guerin (BCG). Two weeks after intraperitoneal challenge with BCG, few bacilli were present in the lungs of wild-type and TLR4(-/-) mice, whereas bacterial loads were tenfold higher in the lungs of infected TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
148
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(160 citation statements)
references
References 32 publications
9
148
2
1
Order By: Relevance
“…Consistent with our observations, the involvement of TLR2 following infection with M. tuberculosis and the ensuing responses of macrophages have been reported previously (21,22,24,25). Because BCG infection-induced ERK phosphorylation was significantly blocked by cytochalasin B or D (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with our observations, the involvement of TLR2 following infection with M. tuberculosis and the ensuing responses of macrophages have been reported previously (21,22,24,25). Because BCG infection-induced ERK phosphorylation was significantly blocked by cytochalasin B or D (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 80%
“…The mammalian innate immune system recognizes invading microorganisms by phagocytic receptors, such as TLRs and b 2 integrin (14)(15)(16)(17)(18). In fact, a role for TLRs in M. tuberculosis infection-induced macrophage death has been reported (19)(20)(21)(22)(23)(24)(25). However, the signaling pathway transmitting TLR activation to macrophage death remains unclear.…”
mentioning
confidence: 99%
“…16 It appears striking that several studies investigating the role of TLRs and TLR associated molecules in mycobacterial infection are divergent in their results. 15,17,[33][34][35][36][37][38][39][40][41][42][43] The results of these studies differ from none, moderate or even strong effects because of the lack of a TLR or TLR associated molecule. To our knowledge, our study is novel in demonstrating that CD14 deficiency results in protection from inflammation induced destruction of the lungs.…”
Section: Discussioncontrasting
confidence: 48%
“…In contrast, studies in which protective roles for TLR2, TLR4 or MyD88 were found, deficiencies of these molecules resulted in exaggerated inflammatory responses most likely because of the increased mycobacterial load, providing a more potent proinflammatory stimulus. 35,[37][38][39][40]42 It remains to be established which signalling receptor(s) mediate the CD14 dependent inflammation observed in WT mice in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Because of the dependence of the induction of EAE on MyD88, adjuvant was required to avoid tolerization. Indeed, mycobacterial PAMPs are recognized by TLR2/6 and TLR4 [20,21], mycobacterial DNA is rich in the TLR9 ligand CpG DNA [22], and PT is recognized by TLR4 [23]. To exclude the potential adjuvant effect of MT-containing CFA and of PT in response to TLR7 ligation, we assessed in vitro the effect of MT and PT on the activation of B cells and BM-derived pDCs.…”
mentioning
confidence: 99%